Banks’ Strategic International Expansion: Evidence from Africa - Elumah, Lucas (Journal of Management Studies and Development, 2023)
This study identified the strategies adopted by banks in Africa to gain access to international markets and why banks establish foreign operations. Twenty-two African banks were selected to examine the entry mode and number of foreign outlets. The study affirmed that most African banks expanded their operations internationally via acquisitions and strategic alliances. At the same time, the motive for expansion is linked to market development to serve customers operating in overseas markets, government policies, and strategic knowledge sourcing. Furthermore, some reasons identified include expanding operations, defensive expansion, and protecting existing bank client relations. The study recommends that African banks should strive to adapt different internationalisation strategies primarily driven by their desire to gain knowledge.